The intersex movement: Empowering through new technologies - Brossi, Lionel (2012)
The aim of this article is to explore the different demands and priorities of the intersex community as displayed in various Internet sites. It focuses on common and divergent viewpoints and strategies associated with the social, medical and legal regulations affecting intersex persons. It also demonstrates how online-based policy-making can lead to real actions and change, by allowing to provide information and support for intersex people, their families and supporters. This is oriented to reduce, if not eliminate, the shame and secrecy surrounding the topic, as well as inform and educate physicians and professionals specialized in intersex issues.